2005
DOI: 10.1136/jnnp.2004.053157
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive deficits in frontotemporal dementia

Abstract: Objectives: To investigate whether metacognitive impairments in self-awareness and self-monitoring occur in patients with frontotemporal dementia (FTD), particularly among those with prominent social and dysexecutive impairments. Methods: Patients diagnosed with FTD were divided by clinical subtype (social-dysexecutive (n = 12) aphasic (n = 15), and constituent subgroups of progressive non-fluent aphasia and semantic dementia) and compared with subjects with probable Alzheimer's disease (AD, n = 11) and age-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
145
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 36 publications
8
145
0
4
Order By: Relevance
“…On the other hand, the subgroup of patients with bvFTD have significant executive-function deficits, 42,43 and it is reasonable to propose that the social disorder in bvFTD is due in part to their executive-resource limitations. Although we demonstrated this in our previous assessments of social problem-solving and self-awareness, 12,15 such associations between social-emotional and executive-cognitive functioning may not have been seen in other work because of limited ascertainment of cognitive measures, such as assessment of a partial range of relevant measures. For example, Lough and coworkers 9,41 examined a limited range of executive measures requiring cognitive estimation, but did not assess measures of mental flexibility that may be a more pertinent cognitive component of empathy.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…On the other hand, the subgroup of patients with bvFTD have significant executive-function deficits, 42,43 and it is reasonable to propose that the social disorder in bvFTD is due in part to their executive-resource limitations. Although we demonstrated this in our previous assessments of social problem-solving and self-awareness, 12,15 such associations between social-emotional and executive-cognitive functioning may not have been seen in other work because of limited ascertainment of cognitive measures, such as assessment of a partial range of relevant measures. For example, Lough and coworkers 9,41 examined a limited range of executive measures requiring cognitive estimation, but did not assess measures of mental flexibility that may be a more pertinent cognitive component of empathy.…”
Section: Discussionmentioning
confidence: 47%
“…Such correlations have been suspected in bvFTD patients on the basis of results of clinical studies, and overlapping pathophysiology that has been identified in focal frontal lesion cases 17 and in previous assessments of social cognition in bvFTD. 12,15 For example, during a three-alternative, forced-choice, social problem-solving task, we identified a significant deficit in bvFTD. Correlational analyses revealed that performance was related to theory of mind, empathy, and cognitive flexibility measures.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations